Evaluation of Tissue-engineered Skin on Base of Human Amniotic Membrane for Wound Healing. Issue 7 (July 2019) - John, Samuel; Kesting, Marco Rainer; Stoeckelhuber, Mechthild; von Bomhard, Achim
Abstract : Background: Human amniotic membranes (hAMs) have shown promising results in recent studies aimed at improving wound healing through several mechanisms. We wanted to investigate its properties as a scaffold by adding autologous cells to treat full-thickness skin defects and hypothesized that recultivated hAM would show an even improved wound healing by accelerating the epidermal closure of the wound. Methods: In an air–liquid cell culture, we cultivated autologous keratinocytes and fibroblasts on the hAM until a mostly keratinized surface was achieved. These hAM, de-epithelialized hAM, native hAM with remaining allogenous cells, and negative controls were compared in the treatment of circular 30 × 30 mm 2 full-thickness skin defects in 4 groups of 6 rats with one wound each. We evaluated the wound contraction every 10 days until wound closure, the macroscopic scar appearance on the Vancouver Scar Scale and the qualitative histological properties of the scar regarding morphology and continuity of the basement membrane. Results: Rats treated with de-epithelialized hAM showed more extent wound contraction ( P < 0.001) than the other 3 groups, which did not differ significantly compared with the control group ( P > 0.05). Vancouver Scar Scale showed no significantly statistical differences between the 4 groups ( P = 0.46). The scar structure of all rats showed similar morphologies, the only difference being the absence of a basement membrane in the negative controls compared with the groups treated with hAM. Conclusion: The rats treated with hAM showed no improved wound healing but a tendency toward a more prominent basement membrane in the resulting scar.